1996
DOI: 10.1007/s002770050203
|View full text |Cite
|
Sign up to set email alerts
|

Stromal abnormalities in neoplastic bone marrow diseases

Abstract: Bone marrow malignancies are clonal disorders resulting from neoplastic transformation of hematopoietic stem or progenitor cells. Similar to their normal counterparts, transformed blood-forming cells remain dependent on signals from the hematopoiesis-regulating stromal environment for survival and proliferation. There is increasing evidence that the microenvironment may also take a more active part in the disease process. A review of the literature on stromal abnormalities in the leukemias, the myelodysplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 72 publications
2
62
0
1
Order By: Relevance
“…39,40 Previous studies have described reduced numbers of colony-forming fibroblasts in AML bone marrow, 6 and our present results support this conclusion and suggest that the number of other important stromal cells may also be reduced in AML. Although the local levels of certain AML-derived cytokines are increased during coculture, the molecular mechanisms behind the AML-induced antiproliferative effect on nonleukemic cells are probably heterogeneous and not caused by a single mediator.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…39,40 Previous studies have described reduced numbers of colony-forming fibroblasts in AML bone marrow, 6 and our present results support this conclusion and suggest that the number of other important stromal cells may also be reduced in AML. Although the local levels of certain AML-derived cytokines are increased during coculture, the molecular mechanisms behind the AML-induced antiproliferative effect on nonleukemic cells are probably heterogeneous and not caused by a single mediator.…”
Section: Discussionsupporting
confidence: 90%
“…[3][4][5][6][7][8][9][10][11][12][13][15][16][17] The molecular bidirectional crosstalk with stromal cells appears to support AML blast proliferation, [3][4][5][6][7][8][9]16,20,22 and our own prior studies demonstrated that both fibroblast cell lines HFL1 and Hs27, the osteoblastic sarcoma cell lines Cal72 and SJSA-1 and normal osteoblasts 33,34 can increase AML blast proliferation as well as release of proangiogenic IL-8 by native human AML cells. Fibroblasts also have an additional antiapoptotic effect, 22 and this effect is observed both with Hs27 and HFL1 fibroblasts (Ryningen, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In malignant diseases, stromal dysfunctions can result from modifications of adhesion molecule expression or growth factor production by stromal cells. 1 Recent data indicate that infection of bone marrow stromal cells by human immunodeficiency virus in vitro lessens their ability to support hematopoiesis. 2,3 Stromal cells are now proposed as targets for gene therapy of some hematological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Leukemia development is a multistep process characterized by progressive cellular transformation of normal hematopoietic stem/progenitor cells into malignant leukemic clones. The functionally abnormal malignant clones become an integral part of the stromal system, selectively stimulating neoplastic cells and inhibiting normal blood cell formation (malignant microenvironment) (Duhrsen & Hossfeld, 1996). Although malignant cells have an intrinsic growth and survival advantage, but they also remain dependent on some factors provided by the malignant microenvironment.…”
Section: Introductionmentioning
confidence: 99%